2014
DOI: 10.1002/alr.21324
|View full text |Cite
|
Sign up to set email alerts
|

Sinonasal mucosal melanoma: 20‐year experience at a tertiary referral center

Abstract: Based on this series, positive margins and the presence of perineural/lymphovascular invasion are negative predictors of survival. In addition, intraoperative frozen section analysis of sinonasal mucosal melanoma correlates well with final pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 18 publications
2
25
0
Order By: Relevance
“…These 2 factors have already been found to have a negative predictive impact on survival in series of mucosal melanoma of the head and neck . Regarding sinonasal malignant melanoma, to the best of our knowledge, the negative prognostic role of positive margins has been identified only in a small series of patients analyzed exclusively by univariate analysis, whereas the association between male sex and worse prognosis was already reported in a retrospective analysis of the Swedish Cancer Registry . The presence of clear margins was significantly associated with pT3, but not with the surgical approach, thus reinforcing the concept that higher T classification lesions are associated with an inherently greater risk of incomplete resection, regardless of the surgical approach.…”
Section: Discussionmentioning
confidence: 63%
“…These 2 factors have already been found to have a negative predictive impact on survival in series of mucosal melanoma of the head and neck . Regarding sinonasal malignant melanoma, to the best of our knowledge, the negative prognostic role of positive margins has been identified only in a small series of patients analyzed exclusively by univariate analysis, whereas the association between male sex and worse prognosis was already reported in a retrospective analysis of the Swedish Cancer Registry . The presence of clear margins was significantly associated with pT3, but not with the surgical approach, thus reinforcing the concept that higher T classification lesions are associated with an inherently greater risk of incomplete resection, regardless of the surgical approach.…”
Section: Discussionmentioning
confidence: 63%
“…Five‐year DFS was 25.2%, and 5‐year OS was 38.1%. Other studies on outcomes of surgically treated patients reported 5‐year OS of 28%‐40.1% . Our relatively high OS might be due to the small number of patients with advanced tumour stage in our cohort.…”
Section: Discussionmentioning
confidence: 64%
“…Perhaps, primary sinus tumours present with more advanced disease at diagnosis, which hampers radical resection. Similar to several other studies, we defined positive margin status as a negative predictor. This emphasises the importance of reliable margin assessment.…”
Section: Discussionmentioning
confidence: 99%
“…3 Several other studies showed associations of positive surgical margins with a higher rate of distant metastases, decreased survival measures, and a significantly higher risk of death compared to patients with negative surgical margins. [43][44][45] Thus, surgeons should consider the complex anatomy of the sinonasal cavity, the proximity of the tumor to vital structures, and the pattern of locally-advanced disease (eg orbital invasion, dural invasion, or brain invasion). It is unclear whether radical surgery, which often comes at the cost of significant cosmetic and functional impairments, is justified.…”
Section: The Molecular Profile Of Snmmmentioning
confidence: 99%